Biochemical Characterization of Ralstonia solanacerum Causing Bacterial Wilt of Brinjal in Bangladesh (Progressive Agriculture, 2013)
Ralstonia solanacearum causes bacterial wilt of solanaceous crop plants including brinjal, a most devastating disease in humid tropic. A survey was conducted on the status of bacterial wilt incidence and severity in major brinjal growing areas and to characterize the isolates of R. solanacearum causing bacterial wilt of brinjal in Bangladesh. The wilt incidence was recorded maximum (22.52) in Rangpur followed by Jessore (20.56) and Panchagarh (20.0) while the lowest wilt incidence was recorded in Jamalpur (6.12). On the contrary, the wilt severity was recorded highest (4.00) in Jhinaidah and the lowest (2.80) was recorded in Jamalpur followed by Jessore (2.93) at the time of survey. The isolates of R. solanacearum were obtained from different locations surveyed were arranged in seven groups based on the location. Grams staining and Potassium hydroxide solubility test revealed that all groups of R. solanacearum isolates are gram negative. The isolates of R. solanacearum fermented four basic sugars (Dextrose,sucrose, manitol and lactose). These results of all biochemical tests in combination with the pathogenicity test confirmed the isolates were R. solanacearum causing bacterial wilt of brinjal. All groups of R. solanacearum isolates were found virulent producing pink or light red color or characteristic red center and whitish margin on TZC medium after 24 hours of incubation. On the biovar test clearly revealed that all groups of R. solanacearum isolates oxidized disaccharides (Sucrose, lactose, and maltose) and sugar alcohols (manitol, sorbitol and dulcitol) within 3-5 days and confirmed biovar as III.Pathogencity test on tomato and chilli indicating wide host range of R. solanacearum isolates and categorized them in race 1. Therefore, it may beconfirmed that R. solanacearum causing bacterial wilt of brinjal in Bangladesh belong to Biovar III and Race 1.DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16744 Progress. Agric. 21(1 & 2): 9 - 19, 2010